2009
DOI: 10.2337/dc09-0207
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Decaffeinated Coffee and the Major Coffee Components Chlorogenic Acid and Trigonelline on Glucose Tolerance

Abstract: OBJECTIVECoffee consumption has been associated with lower risk of type 2 diabetes. We evaluated the acute effects of decaffeinated coffee and the major coffee components chlorogenic acid and trigonelline on glucose tolerance.RESEARCH DESIGN AND METHODSWe conducted a randomized crossover trial of the effects of 12 g decaffeinated coffee, 1 g chlorogenic acid, 500 mg trigonelline, and placebo (1 g mannitol) on glucose and insulin concentrations during a 2-h oral glucose tolerance test (OGTT) in 15 overweight me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(174 citation statements)
references
References 16 publications
5
159
2
5
Order By: Relevance
“…A recent randomised crossover trial, however, showed that chlorogenic acid and trigonelline significantly lower glucose and insulin [37]. This trial supports a mechanism involving these components, but more trials are needed to further elucidate these effects.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent randomised crossover trial, however, showed that chlorogenic acid and trigonelline significantly lower glucose and insulin [37]. This trial supports a mechanism involving these components, but more trials are needed to further elucidate these effects.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of total coffee and tea consumption could indicate that the beneficial effect of coffee and tea consumption is due to their antioxidant content. Coffee is rich in the antioxidant chlorogenic acid and tea contains flavonols and flavones as antioxidants [37,38]. Antioxidants may reduce the amount of reactive oxygen species, which activate stress-sensitive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We observed no differences in the plasma insulin profiles in the present study. Van Dijk et al (2009) reported that, compared to a placebo, ingestion of 5-CQA (1 g) led to significantly lower insulin concentrations 15 min after an oral glucose tolerance test (OGTT) but did not significantly reduce insulin AUC values. In the current study, we obtained similar results, although we did not measure plasma insulin levels at 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Welsch et al (1989) reported that 1 mM chlorogenic acid reduced glucose uptake by approximately 80% in an in vitro brush border membrane system through dissipation of the Na + gradient. Similarly, other studies have shown that chlorogenic acid or chlorogenic acid-rich coffee reduces blood glucose concentration in rats and humans, but these data were obtained from oral glucose tolerance tests (OGTTs) (van Dijk et al, 2009;Thom, 2007). Despite the potential properties attributed to these compounds, little is known about their action in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…У жен-щин наблюдалась даже более значимая связь: риск разви-тия подагры был на 22 и 57% ниже при употреблении 1-3 и более 4 чашек кофе в день соответственно, по сравнению с отсутствием его потребления [98]. Среди возможных ме-ханизмов -снижение инсулинорезистентности (прием ко-фе независимо от наличия кофеина обратно пропорциона-лен сывороточной концентрации С-пептида, а содержаща-яся в кофе хлорогеновая кислота снижает уровень глюкозы и инсулина после перорального приема глюкозы); содер-жащиеся в кофе вещества могут ингибировать ксантинок-сидазу [98,[100][101][102].…”
Section: мясо и морепродук тыunclassified